Impacto do benefício fiscal no apreçamento das debêntures de infraestrutura - Delbem, Fayga Czerniakowski (2016)
The main goal of this paper is to analyze the credit spread impact given by the tax exempt treatment to Brazilian corporate infrastructure bonds introduced in 2011 by law number 12.431. Assuming the non-arbitrage theory, a rational investor would expect that an infrastructure corporate bond credit spread would be equivalent of a regular corporate bond credit spread, adjusted by the tax benefit and others risk factors. However, this paper finds no such evidence for infrastructure corporate bonds. This tax impact is more relevant when we analyze infrastructure corporate bonds sold to retail investors and implies that this asset class is not attractive, on a risk adjusted basis, to investors not eligible for the tax benefit, restricting the demand and development of the capital market infrastructure funding. Due to this, we suggest the possibility of converting the tax exempt bonds in regular bonds and granting the companies with tax subsidy and we believe that it is important to make adjustments in Law number 12.431 to effectively attract private funding to infrastructure financing.